Eficacia de la bilirrubina transcutánea en la hiperbilirrubinemia del recién nacido prematuro HRDT - año 2021 - Loro Gómez, Anggela Pamela (2022)
The use of the transcutaneous bilirubinometer as a non-invasive method is of great predictive value prior to taking serum tests against jaundice in the newborn; and although there are research works that show the sensitivity of transcutaneous bilirubins in newborns, the truth is that most of them have shown us that origin, whether African, Asian, American or any other race influences, as well as gestational age , the days of birth, the place where the sample is taken and many other factors that generate a certain difference in sensitivity, without losing its usefulness. This study aims to describe this sensitivity and other elements that allow me to determine its effectiveness in a Peruvian population.